Training of information retrieval in the State university of Vilnius: some contential and technological aspects of education in the field of librarianship and bibliography - Marija Prokopčik (Knygotyra)
The article deals with the problem of professional education of librarians at the University of Vilnius. The changing role of information, which is becoming one of the natural resources of the country, and the rapid development of computer technology reveal new professional demands for librarians. As a result of this tendency, teaching online bibliographical searching has become of great importance in the library education curriculum.